Scenario planning as a tool to manage tourism uncertainties during the era of COVID-19: a case study of Arizona, USA. Issue 7 (3rd April 2022) - Clark, Connor; Nyaupane, Gyan P.; Timothy, Dallen J.; Buzinde, Christine
ABSTRACT : As the tourism industry faces a long road to full recovery in the wake of the COVID-19 pandemic, this study utilized a scenario planning method to depict widely contrasting conditions in which tourism recovery in the U.S. state of Arizona will need to navigate. To collect data, we held a scenario planning session in June 2020 with 24 participants representing various stakeholder groups, such as public land management agencies, tourism businesses, destination management organizations, and a multidisciplinary panel of experts from the fields of public health, transportation, travel and tourism, and epidemiology. Six critical drivers of tourism recovery were identified, which included public health status, performance of the economy, destination availability, government policy, consumer confidence, and leadership messaging. Among these six critical drivers, public health status and performance of the economy were determined to be the two most influential and most uncertain determinants of tourism recovery and were used to develop four plausible scenarios consisting of a worst-case, best-case and two mid-level scenarios. As social inequities and economic and public health devastation appeared in the scenarios, the crucial methodological contributions and implications for tourism stakeholders, including destination communities, destination managers and local governments, are discussed.